Chemical variables - stream from Feresjön Catchment, main inlet, 2017-06-22–2025-12-08 - Asa Research Station (Swedish University of Agricultural Sciences, 2026)
Manual grab samples from the stream for chemical analysis are taken on a biweekly basis during ice-free conditions, and on a monthly basis in the presence of stream ice.
Asa Research Station (2026). Chemical variables - stream from Feresjön Catchment, main inlet, 2017-06-22–2025-12-08 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/xwQ2J2wPakou3nvqQbUjyN4F
Keywords: Asa Research Station; Stream; Time instant; Time instant; Electrical conductivity; Electrical conductivity; pH; pH; Reference Water temperature for pH measurement; Reference Water temperature for pH measurement; Dissolved organic carbon; Dissolved organic carbon; Total nitrogen; Total nitrogen; Phosphate-P; Phosphate-P; Ammonium-N; Ammonium-N; Nitrate-N; Nitrate-N; Fluorine; Fluorine; Chlorine; Chlorine; Bromine; Bromine; Sulphate-S; Sulphate-S; Lithium; Lithium; Beryllium; Beryllium; Boron; Boron; Sodium; Sodium; Magnesium; Magnesium; Aluminium; Aluminium; Silicon; Silicon; Phosphorus; Phosphorus; Sulfur; Sulfur; Potassium; Potassium; Calcium; Calcium; Vanadium; Vanadium; Chromium; Chromium; Manganese; Manganese; Iron; Iron; Cobalt; Cobalt; Nickel; Nickel; Copper; Copper; Zinc; Zinc; Gallium; Gallium; Arsenic; Arsenic; Selenium; Selenium; Rubidium; Rubidium; Cadmium; Cadmium; Tellurium; Tellurium; Caesium; Caesium; Barium; Barium; Thallium; Thallium; Lead; Lead; Bismuth; Bismuth; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap